(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
This research creation, based on the concepts of Aponte, D. (2019), obeys the systematic exercise of artistic creation, in the line of pedagogy linked to the acts of creation of the didactic group of the performing arts, with the co-production of the Skena Teatro group and the Bachelor of Performing Arts from the Antonio Nariño University and arises from the need to investigate the problematization of the passage from the face-to-face in the theater and the transition to the cinematographic language, we are based on Abuin Gonzáles (2008), for the audiovisual production from a distance. Based on the play “Proyecto Hamlet” rewriting, according to parameters by Juan V. Martínez Luciano (2001, p. 22), a new dramaturgy by Carlos Cárdenas, based on “Hamlet” by William Shakespeare, translated by Luis Astrana Marín, ( 1963). Four monologues are selected for the performance before the camera and the difficulties encountered in the cinematographic narration that will show the development of the fable. It is concluded then that the pandemic opened a way to a new world in virtual learning in the audiovisual area, having an impact from a distance with tools applicable to a globalized world and its social networks as a valuable and powerful alternative for dissemination of scenic creation works. We know that distancing is temporary where it places us in a reflective position to value the other and group work to produce and create art for life.